Radiographic pelvimetry in 0 to 24 month-old pacas (Agouti paca, Linnaeus, 1766) - Smargiassi, N. F. [UNESP]; Lippi, I. C. C. [UNESP]; Oliveira, R. G. S. [UNESP]; Machado, M. R. F. [UNESP]; Sasahara, T. H. C. [UNESP]; Santos, C. C. C. [UNESP]; Oliveira, F. S. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
The pelvimetry consists of the metric determination of the pelvis dimensions and its use is directly related to the reproduction. The cartilage closure time of the ossification centers varies according to the bone, some closing already in the uterine life and others remaining present for many years. The objective was to evaluate, radiographically, the pelvic diameters by pelvimetry during the first 24 months of life in pacas, the second lagest Brazilian rodent and an animal that has shown big recent scientific interest, aiming the estimated age determination. Twelve pacas were used, which were monthly radiographed up from birth until 24 months old, with the animals anesthetized. The pacas are dolicopelvic animals and with pelvis presenting strong tendency to constant growth along the 12 first months of age, fact that can be useful in the approximated animals' age determination that do not have precise birth date, for example.
Keywords: anatomy; radiology; pelvis; rodent; wild